A Longitudinal Study of Lexical Development in Children Learning Vietnamese and English. Issue 2 (19th July 2013) - Pham, Giang; Kohnert, Kathryn
<x xml:space="preserve">Abstract</x> This longitudinal study modeled lexical development among children who spoke Vietnamese as a first language (L1) and English as a second language (L2). Participants (n = 33, initial mean age of 7.3 years) completed a total of eight tasks (four in each language) that measured vocabulary knowledge and lexical processing at four yearly time points. Multivariate hierarchical linear modeling was used to calculate L1 and L2 trajectories within the same model for each task. Main findings included (a) positive growth in each language, (b) greater gains in English resulting in shifts toward L2 dominance, and (c) different patterns for receptive and expressive domains. Timing of shifts to L2 dominance underscored L1 skills that are resilient and vulnerable to increases in L2 proficiency.